Primary retroperitoneal mucinous cystadenocarcinoma in a male patient. Issue 6 (26th May 2006) - Thamboo, T P; Sim, R; Tan, S-Y; Yap, W-M
Abstract : Primary retroperitoneal mucinous cystadenocarcinomas (PRMCs) are rare. This is the first reported case in the literature in English of PRMC in a man. The 64-year-old man presented with a large retroperitoneal cystic tumour measuring 24×20×16 cm 3, which was removed intact. Areas ranging from a benign mucinous cyst to borderline mucinous tumour to mucinous cystadenocarcinoma were observed on microscopy. Strong patchy staining for cytokeratins 7 and 20 and strong diffuse staining for MUC2 and MUC5AC core peptides, similar to staining patterns in ovarian mucinous tumours, were shown in the benign and atypical epithelium. Staining for CA19.9 and carcinoembryonic antigen was also shown by both components. The theory of its origin from the mucinous metaplasia of peritoneal (mesothelial) inclusion cysts, rather than from ectopic ovarian tissue or ovarian teratomas, is supported by the occurrence of such a tumour in a male patient.